Faktor-faktor yang memengaruhi return saham dengan kebijakan dividen sebagai variabel moderasi pada perusahaan sektor energi yang terdaftar di BEI tahun 2018-2022 - Sari, Ira Puspita; Astuti, Diana Dwi; Ilmi, Mainatul (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This study aims to analyze the effect of profitability, leverage, and company size on stock returns and the role of dividend policy as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange for 2018-2022. The sampling technique in this study used a purposive sampling technique, which resulted in 15 companies as research samples from a total population of 84 companies. The data analysis method used is the moderation regression analysis. The results showed that profitability has a significant effect on stock returns. Leverage has no significant effect on stock returns. Company size has no significant effect on stock returns. Dividend policy can act as a moderating variable for the effect of profitability on stock returns. Dividend policy cannot act as a moderating variable for the effect of leverage on stock returns. Dividend policy can act as a moderating variable for the effect of company size on stock returns.